Binding affinity analysis of quinolone and dione inhibitors with Mtb-DNA gyrase emphasising the crystal water molecular transfer energy to the protein–ligand association. Issue 7 (3rd May 2022) - Kumar, G. Siva; Sobhia, M. Elizabeth; Ghosh, Ketan
ABSTRACT: Mtb -DNA gyrase is well known for treating Multidrug-resistant tuberculosis (MDR-TB). The most prevalent single point mutations linked with a high resistance to fluoroquinolones and quinazolinediones in clinical isolates of TB patients are G88A, A90V, S91P, and D94G. The rationale behind the drug resistance due to these mutations is explicated in this study using molecular docking, MD simulations and binding free energy calculations. Molecular docking simulations of fluoroquinolones and quinazolinediones revealed high binding affinity to wild-type Mtb -DNA gyrase, whereas it revealed low binding affinity to mutant variants. The binding free energies for wild, G88A, A90V, S91P, and D94G mutants with fluoroquinolones and quinazolinediones were calculated using the MMGBSA method. This study provides systematic insights into the mechanism behind drug resistance and paves the way to identify potent lead compounds competent across MDR-TB.